Obtaining emulsions of furanocoumarins from Sosnowsky’s hogweed and in vitro assessment of their phototoxic effect - V. I. Shlyapkina; O. A. Kulikov; E. P. Brodovskaya; A. M. Al-khadj Aioub; V. P. Ageev; N. A. Pyataev (Acta Biomedica Scientifica)
Background. Furanocoumarin-based drugs are used for photochemotherapy of various diseases. Sosnovsky’s hogweed can be an available source of furanocoumarins for the development of drugs.The aim of the study. To obtain stable emulsions containing furanocoumarins from Sosnowski’s hogweed and to evaluate their photocytotoxicity.Materials and methods. To obtain the emulsions, furanocoumarins were extracted with chloroform from the sap of the aerial part of the Sosnowski’s hogweed. The chloroform extract was clarified by silica gel gradient column chromatography. The extractive fraction containing furanocoumarins was analyzed by high performance liquid chromatography with ultraviolet (UV) detection. An extract with a high content of 8-methoxypsoralen was used to prepare two types of emulsions. The extract was dissolved in peach oil and emulsified in water with tween-80 (emulsion No. 1) and in an aqueous glycerin solution with lecithin (emulsion No. 2).The emulsions were tested for dark and photo-induced toxicity for human lung fibroblasts. The dose of UV radiation for the photoactivation of furanocoumarins was 9 J/cm2. A solution of chlorine e6 was used as a comparison photosensitizer.Results. The obtained emulsions contained 1 mg/ml 8-methoxypsoralen. Both emulsions were homogeneous at macro- and microscopic visualization, remained stable when stored under various temperature conditions for 14 days. Emulsion No. 2 did not show dark toxicity and caused a statistically significant inhibition of cell viability under UV irradiation at a concentration of 12.5–31.3 µg/mL. Emulsion No. 1 had a toxic effect on cells regardless of UV irradiation due to the content of tween-80. According to fluorescent microscopy, the phototoxic effect of emulsion No. 2 was manifested mainly due to apoptosis, in contrast to the effect of chlorine e6, in which there were more pronounced signs of cell necrosis.Conclusion. The developed experimental emulsions of furanocoumarins from Sosnovski’s hogweed are an example of promising medicinal photosensitizers of plant origin for phototherapy of various dermatological and oncological diseases.